Progress on deuterated potassium dihydrogen phosphate (DKDP) crystals for high power laser system application - Mingxia Xu; Baoan Liu; Lisong Zhang; Hongkai Ren; Qingtian Gu; Xun Sun; Shenglai Wang; Xinguang Xu (Light: Science & Applications, 2022)
Large-aperture high-quality DKDP crystal with deuteration level of 70% has been successfully grown, which can fabricate the large single-crystal optics with the size exceeding 400 mm for ICF application.